Evaluation of tumescent local anesthesia in cats undergoing unilateral mastectomy - Moreira, Clarissa MR.; Oliveira, Renato LS.; Costa, Gilberto A.; Corgozinho, Katia B.; Luna, Stelio PL. [UNESP]; Souza, Heloisa JM. (Elsevier, 2021)
Objective: To evaluate the analgesic efficacy and safety of tumescent local anesthesia (TLA) in cats undergoing unilateral mastectomy. Study design: Prospective clinical trial. Animals: A total of 12 ovariohysterectomized female cats. Methods: All animals were premedicated with pethidine (4 mg kg–1) intramuscularly (IM), followed by induction of anesthesia with propofol (5 mg kg–1) intravenously and maintenance with isoflurane in oxygen. A refrigerated TLA solution (15 mL kg–1, 8 °C) was injected using a Klein cannula. The solution was composed of 0.5 mL of epinephrine (1 mg mL–1) and 40 mL of 2% lidocaine added to 210 mL lactated Ringer's solution (final lidocaine concentration 0.32%). Heart and respiratory rates, systolic arterial blood pressure, temperature and oxygen saturation were measured during anesthesia. Blood samples were collected from the jugular vein for measurement of plasma lidocaine concentration using high performance liquid chromatography. Postoperative pain scores were evaluated hourly for 6 hours. Analgesic rescue was performed with tramadol (2 mg kg–1) IM and meloxicam (0.15 mg kg–1) subcutaneously. Results: Plasma lidocaine concentration peaked at 90 minutes after injection of TLA, but no concentration considered toxic for the species was measured. The median postoperative analgesia time was 6 hours after injection of TLA. Conclusions: This study found that TLA prevented sympathetic response to noxious stimuli during anesthesia and provided satisfactory postoperative analgesia in cats submitted to total unilateral mastectomy, with no apparent signs of toxicity. Clinical relevance: TLA can prevent sympathetic stimulation resulting from noxious stimuli during anesthesia, promoting good intraoperative conditions, proving to be a viable addition to analgesia in cats submitted to a total unilateral mastectomy.
Keywords: analgesia; cat; lidocaine; local anesthesia; mastectomy; tumescent local anesthesia